Pelvic Congestion syndrome - common, but underdiagnosed disease of women - Żyga, Justyna (Journal of Education, Health and Sport, 2022)
Introduction: Pelvic congestion syndrome is defined as the presence of varicose changes in the ovarian veins and venous plexuses associated with chronic pelvic pain syndrome. The main problem with pelvic congestion syndrome is the low awareness of medical staff about this syndrome and the resulting very low recognition. State of knowledge: Pelvic congestion syndrome is an important cause of chronic pelvic pain. The diagnosis is based on imaging examination with ultrasound as a first-line choice and correlation with clinical presentation. The aetiology is multifactorial and may result from a combination of genetic predisposition, anatomical abnormalities, hormonal, mechanical factors with venous wall weakness, reverse blood flow and hypertension. The incidence is strongly related to the number of pregnancies. Conclusions: Pelvic congestion syndrome is one of the possible causes of chronic pelvic pain, thus differential diagnosis should necessarily include venous insufficiency during interviewing, clinical and ultrasound examination of patients. Among several treatment methods, intravascular embolization is a minimally invasive, effective and safe, currently recognised as a method of choice in treatment.